2015
DOI: 10.1021/acscatal.5b01371
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Bifunctional Nature of Pt–Re Catalysts for Selective Glycerol Hydrogenolysis

Abstract: Rhenium substantially promotes the rate of Pt-catalyzed glycerol hydrogenolysis to propanediols and shifts the product selectivity from 1,2-propanediol to a mixture of 1,2 and 1,3-propanediols. This work presents experimental evidence for a tandem dehydration-hydrogenation mechanism that occurs over a bifunctional Pt-Re catalyst. Infrared spectroscopy of adsorbed pyridine and the rate of aqueous-phase hydrolysis of propyl acetate were used to identify and quantify Brønsted acid sites associated with the Re com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 90 publications
8
103
0
3
Order By: Relevance
“…The Ir 4f spectrum shows the binding energies (BE) for 4f 7/2 and 4f 5/2 peaks at approximately 60.8 and 63.8 eV, respectively,i ndicating Ir exists in the metallics tate. [66] The analysiss uggestsa significant portion of Re is partially reducedt oR e 2 + ,R e 4 + ,a nd Re 6 + (27 %, 17 %, and 4%,r espectively), which is consistent with our prior report of the Ir-ReO x /SiO 2 -catalyzed HDO of high-carbon furylmethanes. [66] The analysiss uggestsa significant portion of Re is partially reducedt oR e 2 + ,R e 4 + ,a nd Re 6 + (27 %, 17 %, and 4%,r espectively), which is consistent with our prior report of the Ir-ReO x /SiO 2 -catalyzed HDO of high-carbon furylmethanes.…”
Section: Reaction Network and Proposed Mechanismsupporting
confidence: 89%
“…The Ir 4f spectrum shows the binding energies (BE) for 4f 7/2 and 4f 5/2 peaks at approximately 60.8 and 63.8 eV, respectively,i ndicating Ir exists in the metallics tate. [66] The analysiss uggestsa significant portion of Re is partially reducedt oR e 2 + ,R e 4 + ,a nd Re 6 + (27 %, 17 %, and 4%,r espectively), which is consistent with our prior report of the Ir-ReO x /SiO 2 -catalyzed HDO of high-carbon furylmethanes. [66] The analysiss uggestsa significant portion of Re is partially reducedt oR e 2 + ,R e 4 + ,a nd Re 6 + (27 %, 17 %, and 4%,r espectively), which is consistent with our prior report of the Ir-ReO x /SiO 2 -catalyzed HDO of high-carbon furylmethanes.…”
Section: Reaction Network and Proposed Mechanismsupporting
confidence: 89%
“…Although recent work has shown that surface carboxylic intermediates adsorbed on metal surface might influence the position where C−O cleavage rupture occurs, it is still generally accepted that catalyst structures are crucial for both activity and selectivity towards 1,3‐PDO formation during glycerol hydrogenolysis. To date, there are two types of bimetallic nanocatalysts which display promising performances for 1,3‐PDO formation (Scheme ) . Re promoted Rh and Ir bimetallic catalysts show good selectivity towards 1,3‐PDO under very mild conditions .…”
Section: Figurementioning
confidence: 99%
“…24,28 Alternatively, it has also been suggested that CO is removed via the enhanced WGS activity at ReO x sites on the Pt−Re/TiO 2 catalysts. 12,13,16 Superior properties for the Pt−Re catalysts have been observed in reactions associated with biomass reforming, such as glycerol hydrogenolysis to propanediols 23,29 and selective hydrogenation of carboxylic acids 30,31 and aldehydes 32 to alcohols. In addition, a number of studies report unusual and desirable chemical activity for the bimetallic Pt−Re surfaces.…”
Section: ■ Introductionmentioning
confidence: 99%